Seni Post-Internet dan Pengaruhnya terhadap Persepsi Kesehatan Mental Remaja - Salmalika Savita; Agus Juhana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Digital art communities on the internet connect artists, creators, and art enthusiasts globally to share and discuss digital artworks. Through platforms like Facebook, Instagram, Discord, and Pinterest, artists can showcase their work to an international audience, strengthening social connections and supporting mental health. Art, including digital art, helps teenagers express themselves, communicate, and grow emotionally and socially. Additionally, technology in art therapy creates enjoyable experiences that foster creativity. This study uses systematic literature review (SLR) to gather relevant evidence, but research on the use of digital media in art therapy for teenagers with diverse issues is still limited, requiring further exploration. The study also highlights global interest in the relationship between art, technology, and adolescent development, emphasizing the great potential of art and technology in improving social and emotional well-being.